Graphene market gets a boost from novel production method. (Research'eu results magazine)
Whilst there is no denying the potential of graphene, its mass production has so far been hindered by laborious fabrication methods and the high costs they entail. A new technique developed by partners of the CARERAMM project promises to overcome these problems.